The epidemiology of Aedes-borne arboviral diseases in Zhejiang, Southeast China: a 20 years population-based surveillance study - Ren, Jiangping; Chen, Zhiping; Ling, Feng; Liu, Ying; Chen, Enfu; Shi, Xuguang; Guo, Song; Zhang, Rong; Wang, Zhen; Sun, Jimin (Frontiers in Public Health, 2023)
Objective: Aedes-borne arboviral diseases were important public health problems in Zhejiang before the coronavirus disease 2019 (COVID-19) pandemic. This study was conducted to investigate the characteristics and change of the epidemiology of Aedes-borne arboviral diseases in the province. Methods: Descriptive analyses were conducted to summarize the epidemiology of Aedes-borne arboviral diseases during 2003–2022. Results: A total of 3125 cases, including 1968 indigenous cases, were reported during 2003–2022. Approximately three-quarters of imported cases were infected from Southeast Asia. The number of annual imported cases increased during 2013–2019 (R2 = 0.801, p = 0.004) and peaked in 2019. When compared with 2003–2012, all prefecture-level cities witnessed an increase in the annual mean incidence of imported cases in 2013–2019 (0.11–0.42 per 100,000 population vs. 0–0.05 per 100,000 population) but a drastic decrease during 2020–2022 (0–0.03 per 100,000 population). The change in geographical distribution was similar, with 33/91 counties during 2003–2012, 86/91 during 2013–2019, and 14/91 during 2020–2022. The annual mean incidence of indigenous cases in 2013–2019 was 7.79 times that in 2003–2012 (0.44 vs. 0.06 per 100,000 population). No indigenous cases were reported between 2020–2022. Geographical extension of indigenous cases was also noted before 2020—from two counties during 2003–2012 to 44 during 2013–2019. Conclusion: Dengue, chikungunya fever, zika disease, and yellow fever are not endemic in Zhejiang but will be important public health problems for the province in the post-COVID-19 era.